Courtesy and its features In the poetry of the Andalusians (Journal of the College of Basic Education, 2022)
This study, which the researcher was concerned with, came as a modest attempt to prove the prevalence of the phenomenon of courtship in the poetry of Andalusian women *, especially spinning from it. This phenomenon that we are almost null in our Levantine literature, as women often become the student, not the one required in spinning poetry, unlike the Levantine woman who appears in Spinning as required, not requesting.It is the study of the production of the poetry of Andalusia, which was facilitated by the various sources, that led to monitoring, defining and addressing this phenomenon by looking at the available poetic texts.